1994
DOI: 10.1093/ajcp/101.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Sampling Accounts for the Increased Diagnostic Accuracy Using the ThinPrepProcessor

Abstract: Recent clinical trials indicated that the ThinPrep method of sample preparation has greater diagnostic sensitivity than the conventional direct Papanicolaou smear. The authors hypothesized that nonhomogeneous cell sampling during transfer from the sampling device to the microscope slide was a contributing factor to the reduced accuracy of the conventional direct Pap smears in these trials. To test this hypothesis, four direct smear methods were compared with the newly developed, fluid-based, filter-transfer me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
160
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(168 citation statements)
references
References 0 publications
3
160
0
5
Order By: Relevance
“…A commonly cited advantage of LBC is that, unlike conventional smears, for which only a selective portion of cellular material is transferred to the slide, almost all sampled cells are rinsed into the liquid and dispersed throughout. 28 As a result, LBC is thought to produce smears that are more representative of the entire sample, thereby, facilitating the detection of abnormal cells when only a few such cells have been adequately sampled.…”
Section: Discussionmentioning
confidence: 99%
“…A commonly cited advantage of LBC is that, unlike conventional smears, for which only a selective portion of cellular material is transferred to the slide, almost all sampled cells are rinsed into the liquid and dispersed throughout. 28 As a result, LBC is thought to produce smears that are more representative of the entire sample, thereby, facilitating the detection of abnormal cells when only a few such cells have been adequately sampled.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hutchinson et al [32], more than 80% of collected cells from the cervix are not deposited in the glass slides. Moreover, it is not possible for gynecologists to select a representative sample for the slide.…”
Section: Discussionmentioning
confidence: 99%
“…15 The enhanced detection of epithelial cell abnormalities by TP is due in part to improved sampling and a lack of obscuring blood, inflammation, and mucus. 26 There are only a few studies addressing interob- server variability in diagnosing gynecologic cytology using TP. In a recent study, 3 pathologists and 1 senior cytotechnologist reviewed 144 TP slides previously diagnosed as WNL, ASCUS, and SIL.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the epithelial cells in the conventional cervical smears often were distributed unevenly over the slide and aggregated in overlapping groups, whereas the TP cervical slides displayed cells that were distributed more evenly within a 22-mm circle and with minimal overlap. 26,27 Better cell preservation and visualization due to lack of air-drying artifacts and obscuring inflammation and blood also contributed to the improved quality of TP. 14,15,27 A recent study reported an increase in the rate of completely satisfactory specimens from 80% to 90% and a decrease in the rate of satisfactory but limited by… findings by 46% with the use of TP.…”
Section: Discussionmentioning
confidence: 99%